The Impact of Team Mindfulness on Project Team Performance: The Moderating Role of Effective Team Leadership. Issue 2 (April 2023) - Majeed, Mehwish; Irshad, Muhammad; Khan, Ikram; Saeed, Imran
The current study aims to investigate the consequences of team mindfulness in project-based organizations by proposing team cohesion as an underlying mechanism and effective team leadership as a boundary condition through which team mindfulness promotes project team performance. Data were collected through a time-lagged survey from Pakistani employees (N = 379). The data supported the proposed model revealing that team mindfulness enhances team cohesion among employees, which increases project team performance and effective team leadership moderates this relationship. This study has identified the team-level factors that can be used by project managers to increase project team performance.